2020
DOI: 10.3390/jcm9113712
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density, Osteoporosis, and Fracture Risk in Adult Patients with Psoriasis or Psoriatic Arthritis: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Introduction: Awareness of psoriasis-related comorbidities has been established in the current guidelines; however, evidence regarding the association of bone density or bone fragility with psoriatic disease remains inconclusive. Methods: We conducted a systematic review and meta-analysis to assess bone mineral density and the risk of osteoporosis and fractures in patients with psoriatic disease, including those with cutaneous psoriasis and psoriatic arthritis. We searched electronic databases for published ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 62 publications
1
21
0
3
Order By: Relevance
“…A previous analysis concluded that psoriatic patients have a higher fracture risk than non-psoriatic controls [11]. Furthermore, lower vBMD in psoriatic patients may be related to lower bone quality and contributes to the higher risk of fracture [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous analysis concluded that psoriatic patients have a higher fracture risk than non-psoriatic controls [11]. Furthermore, lower vBMD in psoriatic patients may be related to lower bone quality and contributes to the higher risk of fracture [35].…”
Section: Discussionmentioning
confidence: 99%
“…In recent experimental and clinical research, abnormal bone remodeling and new bone formation in psoriatic disease have turned research attention to bone health in psoriatic comorbidities [9,10]. A previous study concluded that psoriatic patients have a higher fracture risk than non-psoriatic controls, without necessary association with lower bone mineral density (BMD) [11]. BMD defined by the commonly used dual-energy X-ray absorptiometry (DXA), which only measures areal BMD (aBMD), may not reflect the actual bone strength [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a second approach they found that the prevalence of psoriasis was significantly higher in osteoporosis patients than in controls (122). A meta analysis showed an increased risk of fractures in patients with psoriasis/psoriatic arthritis (124,125). Raimondo et al showed increased serum RANKL levels and osteoclast differentiation as well as activity in monocytes from psoriatic patients with severe skin disease in comparison to those with mild skin disease (42).…”
Section: Epidemiological Association Of Bone Metabolism and Chronic I...mentioning
confidence: 99%
“…In a second approach they found that the prevalence of psoriasis was significantly higher in osteoporosis patients than in controls ( 122 ). A meta analysis showed an increased risk of fractures in patients with psoriasis/psoriatic arthritis ( 124 , 125 ). Raimondo et al.…”
Section: Epidemiological Association Of Bone Metabolism and Chronic I...mentioning
confidence: 99%
“…The role of VD in PsA is controversial; in fact, only some studies provide evidence of a correlation between VD deficiency and PsA severity [77], despite the role of VD in decreasing the production of IL-2, IL-6, and interferon-gamma and reducing the inflammatory pathway promoting suppressor T-cell activity being widely demonstrated. However, subjects affected by PsA show low serum 25(OH)D levels, with concentrations lower than 20 ng/mL, and, in some studies, OP is one of the major comorbidities of PsA, with a prevalence of 1.4-68.8% [78]. In fact, it is known that the alteration of bone metabolism in this pathology involves both resorption and bone neoformation (ankylosis, periostitis, and syndesmophytes).…”
Section: Autoimmune Diseases Vd Deficiency and Opmentioning
confidence: 99%